The use of the educational game as a supportive therapy in stays outside care centers - Vargiu, Yuri (Formazione & insegnamento, 2019)
During the various programs carried out within day centers, communities or RSA, trips or stays are often inserted at vacation places, such as mountains and sea, in which to spend time in contact with other people and in general with nature. The problems often overlooked or not considered by these beautiful initiatives, however, risk to impoverish the therapeutic treatment making it even harmful. The use of structured play activities can facilitate acclimatization and socialization, giving the educator or specialist the possibility to export and verify the skills learned by the guest outside the center.